The capabilities of secondary school teachers to provide financial education. (August 2019) - De Beckker, Kenneth; Compen, Boukje; De Bock, Dirk; Schelfhout, Wouter
This study examines the capabilities of in-service secondary school teachers to provide financial education. Data were gathered from online surveys, which were spread among 300 teachers in the Flemish region of Belgium. We distinguish between perceived and actual capabilities. Our results reveal that only one third of teachers consider themselves sufficiently competent to provide financial education. Actual capabilities are assessed using a broad measure of financial literacy, which takes into account teachers' financial knowledge, financial behaviour and financial attitudes. Our results indicate that only approximately half of teachers score sufficiently on financial knowledge and only a third attains the preferred minimum score for financial attitudes. In addition, our heterogeneity analysis shows differences in scores related to teacher characteristics such as gender, teaching discipline and teaching experience. The large share of teachers not reaching the threshold indicating adequate capabilities for providing financial education raises concern, as teacher quality is an important factor contributing to the effectiveness of financial education. Teacher professional development can play a crucial role here.